A Review Article On Vicharchika - A Twak Vikar - Neha; Sood, Sanjeev; Sharma, Chander Shekhar; Sharma, Amrita (International Research Journal of Ayurveda & Yoga, 2021)
Skin is the most pervasive sense organ that covers the whole outside of the body, forming a protective barrier against pathogens and injuries from the environment. It puts light on our physical, general health and wellbeing of an individual. In Ayurveda, all types of skin diseases can be considered under the shelter of Kushtha Roga (Skin diseases) and Vicharchika (Eczema) is one Twaka Vikara (Skin Diseases) explained under Kshudra Kushtha (Minor skin diseases). The clinical presentation of Vicharchika (Eczema) viz.Kandu(itching), pidaka(vesicles), Srava (Discharge) and Shvayavarna(discoloration) resembles to eczema in modern dermatology. It is not life-threatening disease but affects psychological health causing anxiety, depression, disturbs the person’s routine thus interrupts the ability to function normally, lead to social isolation and also disturbs quality of life. Modern science has advanced techniques & treatment but for the cure of eczema there is no satisfactory treatment, antihistamines and steroids are mostly used which shows various side effects. In Ayurveda Shodhan (Purification) is the best therapeutic procedure to eradicate the root cause of the disease and in Kushtha (Skin diseases) repeated Shodhna (Purification) is indicated to balance the vitiated Dosha. Amid Shodhan (Purification) therapy Virechan Karam (Purgation) described in ancient texts is mainly prescribed and it doesn’t only cleanse the intestine but has multiple systemic benefits. Acharya Charak has indicated Virechan Karma (Purgation) for Pittaj and Rakatj Dushti. Hence the best possible treatment in Vicharchika (Eczema) is Shodhan (Purification) followed by Shamana therapy (Pacification). The present paper emphasizes on the various aspects of Vicharchika (Eczema) explained in ancient Ayurvedic texts.